Parachute mitral valve assessed by cardiac magnetic resonance - Casavecchia, Grazia (Interv Med Appl Sci, 2019)
Parachute mitral valve (PMV) is a congenital cardiac malformation where typically all tendons chordae converge and insert into one major papillary muscle. We report the case of 27-year-old man affected by Hodgkin’s lymphoma-mixed cellularity subtype with polychemotherapy treatment and Barrett’s esophagus who came to our attention for routine echocardiographic exam and evaluation of left ventricular function. In the presence of normal left ventricular systolic function and mild-moderate mitral regurgitation, a careful examination of mitral apparatus showed a single papillary muscle suspected for PMV. In the presence of Barrett’s esophagus, the patient was further assessed cardiac magnetic resonance (CMR) that confirmed the diagnosis of PMV and excluded other associated congenital anomalies. Despite the rare incidence of PMV and a diagnosis generally based on transesophageal echocardiography, CMR could represent a useful tool, in selected cases, to confirm the diagnosis of PMV, identify other possible congenital anomalies, and assess ventricular and valvular function.